Characterization of key genes of the renin–angiotensin system in mature feline adipocytes and during in vitro adipogenesis. Issue 6 (9th October 2015) - Riedel, J.; Badewien‐Rentzsch, B.; Kohn, B.; Hoeke, L.; Einspanier, R.
Summary: Obesity is a growing health problem in humans as well as companion animals. In the development and progression of obesity‐associated diseases, the members of the renin–angiotensin system (RAS) are proposed to be involved. Particularly, the prevalence of type 2 diabetes mellitus in cats has increased enormously which is often been linked to obesity as well as to RAS. So far, reports about the expression of a local RAS in cat adipocytes are missing. Therefore, we investigated the mRNA expression of various RAS genes as well as the adipocyte marker genes adiponectin, leptin and PPAR‐ γ in feline adipocytes using quantitative PCR. To characterize the gene expression during adipogenesis, feline pre‐adipocytes were differentiated into adipocytes in a primary cell culture and the expression of RAS key genes measured. All major RAS components were expressed in feline cells, but obvious differences in the expression between pre‐adipocytes and the various differentiation stages were found. Interestingly, the two enzymes ACE and ACE2 showed an opposite expression course. In addition to the in vitro experiments, mature adipocytes were isolated from subcutaneous and visceral adipose tissue. Significant differences between both fat depots were found for ACE as well as AT1 receptor with greater expression in subcutaneous than in visceral adipocytes. Visceral adipocytes had significantly higher adiponectin and PPAR‐ γ mRNA level compared to the subcutaneous fat cells. Concerning the nutritional status, a significant lower expression of ACE2 was measured in subcutaneous adipocytes of overweight cats. In summary, the results show the existence of a potentially functional local RAS in feline adipose tissue which is differentially regulated during adipogenesis and dependent on the fat tissue depot and nutritional status. These findings are relevant for understanding the development of obesity‐associated diseases in cats such as diabetes mellitus.